Análise da variabilidade vertical do solo com técnicas de agricultura de precisão - Camargo, Bianca Rodrigues (2023)
Precision agriculture is a precise allocation of resources, inputs and tasks within the crop, in which the use of digital tools can enhance the benefits of this system. In this sense, the present research analyzed the vertical variability of some chemical characteristics of the soil, analyzing and evaluating their behavior under different sampling depths. The general objective of the study was to quantify and measure the vertical variability of the elements Phosphorus (P) and Potassium (K), in subsurface layers of different types of management, located in two Brazilian states, Mato Grosso and Bahia, through field examples. Based on the methodological paths carried out throughout the research, the characteristics of an analysis bank of georeferenced Precision Agriculture samples are highlighted, analyzing their particularities, presenting the analytical and descriptive results of 4 properties adopting Precision Agriculture. Thus, the results for elements (P) and (K) showed a vertical gradient considered important in the soil profile. It is concluded, then, that the evaluation of fertility profiles reflected the imbalances that are occurring in areas of grain cultivation under direct planting, with simple strategies being presented to help the areas and the variability of the elements found.